At the Crossroads between Opera and Oratorio: Biblical Themes and 19ᵗʰ Century French Opera - KARÁCSONY, Noémi; RUCSANDA, Mădălina Dana (Studia Universitatis Babes-Bolyai Musica, 2023)
The present study aims to investigate the delicate border between oratorios and operas based on biblical subjects, focusing on French music. A brief analysis of the period prior to the 19th century reveals that the oratorio was not one of the most popular genres in France, allowing the genesis of various genres inspired by biblical subjects. The oratorio enjoyed a brief revival in the 18th century, leading in the 19th century to the composition of biblical operas and the dawn of genres that are at the crossroads between opera and oratorio: mystére, drame sacré, or légende sacrée, represented by works of Jules Massenet. Although traditionally referred to as oratorios, these works allowed for staged representation, due to the dramatic qualities of the librettos, which in turn allowed for the musical discourse to depart from the sobriety of the oratorio and to include certain features that are characteristic for opera. Gradually, biblical subjects began to be tackled in operas as well, as will be seen in the works of Camille Saint-Saëns and Jules Massenet, the two composers on whose works the present study mainly focuses. At the same time, biblical themes can be related to musical orientalism, but also to the fin de siècle decadent aesthetic (through their exploration of such themes as the opposition between sacred and erotic love), serving as mirror for the political, social, and religious context of the Third Republic.